Considering inheritance as one of the consequences of the soul body relationship in Aquinas, Avicenna, and Mulla Sadra - Mohammad Kazem Elmi Sola; Sahebi, Tooba La’L; Amir Rastin Toroghi (Penerbit Universiti Kebangsaan Malaysia, 2022)
Inheritance is one of the most important issues that has been discussed empirically in genetics since the late nineteenth century. One proper philosophical context of such issue can be traced back in the body-soul relationship debate. This paper goes through the position of Aquinas, Avicenna, and Mulla Sadra, as three different Aristotelian philosophers, to examine how their thought in the issue of soul-body relationship can open a window to the matter of inheritance and which one can better prepare a philosophical ground for such empirical topic. According to Aristotle, the soul is the form of the body, and the body is the soul’s matter. This necessitates a mutual relationship. Although accepting this relationship, both Avicenna and Aquinas disagree with Aristotle on the problem that how the soul can be an immaterial component. But according to Mulla Sadra, basically, the matterform relationship deepens and even indicates a kind of unity in a graded reality. This means that it is a longitudinal relationship–the soul is the continuation of the existence of its own body and is its higher level, not something strange and independent. Therefore, whatever exists in the body, exists in the soul and hence, the role of matter in inheritance becomes more meaningful.